2010
DOI: 10.3109/03009741003781951
|View full text |Cite
|
Sign up to set email alerts
|

Impaired regulatory T-cell homeostasis due to vitamin D deficiency in undifferentiated connective tissue disease

Abstract: Our findings support the idea that vitamin D influences the Th17/nTreg imbalance in vitamin D-insufficient patients with UCTD and could be beneficial in the management of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 58 publications
0
17
0
3
Order By: Relevance
“…Measurement of IL-17 producing T cells was performed to strengthen the diagnosis of STAT3-HIES patients as described previously [15].…”
Section: Evaluation Of Intracellular Il-17 By Flow Cytometrymentioning
confidence: 99%
“…Measurement of IL-17 producing T cells was performed to strengthen the diagnosis of STAT3-HIES patients as described previously [15].…”
Section: Evaluation Of Intracellular Il-17 By Flow Cytometrymentioning
confidence: 99%
“…Deficiency in 25(OH)D may lead to hypocalcemia, hyperparathyroidism, and diminished bone mineral density/content. Vitamin D deficiency has also been associated with multiple systemic effects including elevated blood pressure [15, 16], metabolic syndrome, cardiovascular disease [17], anemia [18], and impaired immune system regulation [19]. …”
Section: Introductionmentioning
confidence: 99%
“…(50) Importantly, Zold et al showed that the UCTD patients with the lowest vitamin D levels were the ones who tended to transition to a defined connective tissue disease (50) and that low vitamin D levels in UCTD patients impaired regulatory T-cell homeostasis. (51) …”
Section: Introductionmentioning
confidence: 99%